2021
DOI: 10.1016/j.aninu.2020.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Source of fiber influences growth, immune responses, gut barrier function and microbiota in weaned piglets fed antibiotic-free diets

Abstract: This study examined the impacts of different fiber sources on growth, immune status and gut health in weaned piglets fed antibiotic-free diets. Sixty piglets (BW = 8.18 ± 1.35 kg) were assigned to 3 dietary treatments based on BW and gender in a randomized complete block design (5 replicates/treatment and 4 piglets [2 barrows and 2 gilts]/replicate): (1) an antibiotic-free diet (control, CON); (2) CON + 6% wheat bran (WB); (3) CON + 4% sugar beet pulp (SBP). Dietary WB supplementation tended to increase ADG co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
(51 reference statements)
8
13
0
Order By: Relevance
“…Note that the concentration of a dietary fiber is important, because the intestinal filling caused by high fiber diets could reduce voluntary intake and affect the energy intake of a pig [ 39 ]. In this trial, 5% concentration of all the four fibers did not affect the feed intake of piglets, which was consistent with previous studies [ 47 ]. Zhao et al reported that the concentration of 5% WB had beneficial effects on the growth performance and intestinal microflora of weaned piglets [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Note that the concentration of a dietary fiber is important, because the intestinal filling caused by high fiber diets could reduce voluntary intake and affect the energy intake of a pig [ 39 ]. In this trial, 5% concentration of all the four fibers did not affect the feed intake of piglets, which was consistent with previous studies [ 47 ]. Zhao et al reported that the concentration of 5% WB had beneficial effects on the growth performance and intestinal microflora of weaned piglets [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is supported by Batson et al ( 2021 ), who demonstrated that piglets fed different fiber source had no change in growth performance, but pigs fed added cellulose had increased fecal DM. In addition, these findings suggest that DF treatment could reduce the diarrhea rate in piglets, which is consistent with the findings of Shang et al ( 2021 ). The results of this study showed that the testes exhibited temporal and spatial changes with the development of growing boars.…”
Section: Discussionsupporting
confidence: 92%
“…Note that the dosage of dietary ber is important, because the intestinal lling caused by high ber diets reduces the voluntary intake and affects the energy intake of the pig [28]. In this trial, 5% doses of all four bers with different WBC and fermentability did not affect the feed intake of piglets, which was consistent with previous studies [32]. Zhao et al, reported that the dosage of 5% WB had bene cial effects on the growth performance and intestinal micro ora of weaned piglets [33].…”
Section: Discussionsupporting
confidence: 90%